Expanding indigent people’s right of access to justice and fair trial through a limited right of legal representation by paralegals in Malawi - Killander, Magnus (University of Pretoria, 2023)
Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2023.